Shortest Path Computation on Air Indexes - KELLARIS, Georgios (Institutional Knowledge at Singapore Management University, 2010)
Shortest path computation is one of the most common queries in location-based services that involve transportation net- works. Motivated by scalability challenges faced in the mo- bile network industry, we propose adopting the wireless broad- cast model for such location-dependent applications. In this model the data are continuously transmitted on the air, while clients listen to the broadcast and process their queries locally. Although spatial problems have been considered in this environment, there exists no study on shortest path queries in road networks. We develop the rst framework to compute shortest paths on the air, and demonstrate the practicality and e ciency of our techniques through exper- iments with real road networks and actual device speci ca- tions.